The Application of Behavioral Architecture Design in the Design of Rusunawa as a Sustainable and Affordable Housing Alternative in Surabaya - Shabilla Rahin Jatmiko; Wiwik Widyo Widjajanti; Suci Ramadhani (Jurnal IPTEK, 2025)
The city of Surabaya is the capital of East Java Province. As a result, villagers looking for work are turning to the city. This triggered a large migration flow and the need for housing, leading to the emergence of illegal settlements in urban areas. One of them is Dupak Magersari Village, Jepara Village, Bubutan District. To overcome this problem, the government provides decent housing for low-income people (MBR) in the form of rental flats (rusunawa). However, low-cost flats often face issues such as poor maintenance, leaky roofs and pipes, and uncomfortable living environments. Therefore, behavioral architecture approaches are used in the planning and design of rusunawa as an alternative to sustainable and affordable living. This approach considers the relationship between a person's behavior and the surrounding environment. The design is made through macro and micro studies, such as accessibility for all groups, connectivity between buildings, forms that adapt to the concept of village, and flexible shared spaces according to the needs of residents. It is hoped that its implementation can create a safe and comfortable environment to live in, in harmony with the surrounding community and nature.